Pendidikan Agama untuk Perlindungan Anak Kelompok Rentan di Kota Besar - Nazihah; Nazihah, Nazihah; Thoriq Majid (Jurnal Studi Gender dan Anak, 2025)
Vulnerable children have the right to protection, and one of the ways to ensure this protection is through education. Religious education offers moral and social values, guidelines for interaction, perspectives, skills, and attitudes that support both individual and social life. Using a descriptive qualitative approach and a case study method, this research aims to provide a detailed account of the implementation of religious education for street children, scavenger children, and orphans—who are categorized as vulnerable children—in Jakarta and South Tangerang. The study concludes that religious education, as an effort to protect vulnerable children in major urban areas, is divided into two forms as learning activities and extracurricular activities. Both forms play a critical role in fostering awareness and acceptance of the child’s identity, both by the children themselves, their families, and the broader community.